Moving up the Waste Hierarchy in Maine: Learning from “Best Practice” State-Level Policy for Waste Reduction and Recovery - Isenhour, Cindy; Blackmer, Travis; Wagner, Travis; Silka, Linda; Peckenham, John; Hart, David; MacRae, Jean (Maine Policy Review, 2016)
As Maine residents look toward the future, it is increasingly clear that more sustainable waste and materials management solutions will be necessary. A recent stakeholder engagement process involving nearly 200 industry professionals, municipal representatives and citizen groups confirmed this point. As we move together toward a more sustainable waste management system, participants in the engagement process identified an outstanding need to learn more about policies options. This article responds to that need with a review of state level policies designed to reduce waste generation and increase material recovery rates. We find there are a wide variety of state-level policy tools available, each of which involves a series of complex tradeoffs to balance decision criteria ranging from diversion potential and cost to social acceptability and environmental protection. While there is no magic formula, it is clear that the most successful state-level programs are those that utilize a variety of tools, selected as part of a comprehensive and data-driven long term planning process.
Keywords: waste management; sustainability; policy; environment; Maine